2021
DOI: 10.3233/jifs-189200
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the future price of a commodity using the OWMA operator: An approximation of the interest rate and inflation in the brown pastusa potato price

Abstract: This main aim of this paper is to propose a methodology for the prediction of the future price of the brown pastusa potato in Colombia, taking into consideration the variables of interest rate, as measured by fixed term deposits (FTDs), and inflation rate, as measured by the consumer price index (CPI). The methodology conducts linear regression analysis and assesses the results using the significance test, the Durbin-Watson statistic, analysis of the variance inflation factor (VIF) and the coefficient of deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Fonseca-Cifuentes et al identified the large impact of interest rates on the future price of Colombian brown potatoes by using methods such as significance tests and OWMA. And both potatoes and wheat are bulk commodities with certain common characteristics [10]. Therefore, the model currently developed does not explain 100% of the behaviour of price changes in the wheat futures market.…”
Section: Introductionmentioning
confidence: 99%
“…Fonseca-Cifuentes et al identified the large impact of interest rates on the future price of Colombian brown potatoes by using methods such as significance tests and OWMA. And both potatoes and wheat are bulk commodities with certain common characteristics [10]. Therefore, the model currently developed does not explain 100% of the behaviour of price changes in the wheat futures market.…”
Section: Introductionmentioning
confidence: 99%
“…For example, along the IOWA operator line, many proposals have taken a variety of approaches, which have used linguistic variables [18,19], fuzzy preference [20], intuitionistic fuzzy sets [21][22][23], distance measures [24,25], and heavy and prioritized operators [16,26,27], with others applying means such as Bonferroni means [28], VIKOR [29], Choquet [30], etc. For the OWMA operator, [31] generalized moving averages, distance measures and OWA; [16] proposed induced heavy moving averages, which can be applied in forecasting approaches [17,[32][33][34]. Finally, the Pythagorean membership grade operator has focused on Pythagorean fuzzy sets, which have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%